The farmer's benevolent trust : law and agricultural cooperation in industrial America, 1865-1945 - Woeste, Victoria Saker (Chapel Hill ; London : The University of North Carolina Press, 1998)
Farmer''s Benevolent Trust: Law and Agricultural Cooperation in Industrial America, 1865-1945.
8: Decline of the Benevolent TrustPart Four: Cooperation in the Industrial Economy 1920-1945; 9: Associationalism and Regulation; 10: From Administered Markets to Public Monopoly; Conclusion; Appendix: A Statistical Profile of Small Farms in California, 1850-1940; Notes; Bibliography; Index.
Includes bibliographical references (pages 335-356) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Online resource (HeinOnline, viewed August 30, 2016).
English.
Keywords: California Associated Raisin Company; California Associated Raisin Company; California Associated Raisin Company; California Associated Raisin Company; Agriculture, Cooperative -- Law and legislation -- United States -- History; Raisin industry -- Law and legislation -- California -- History; Coopératives agricoles -- Droit -- États-Unis -- Histoire; Raisins secs -- Industrie -- Droit -- Californie -- Histoire; LAW -- Administrative Law & Regulatory Practice; Agriculture, Cooperative -- Law and legislation; Raisin industry -- Law and legislation; California; United States; Landbouwbedrijven; Industrialisatie; Samenwerkingsvormen (bedrijfseconomie); Juridische aspecten; Landwirtschaftsgenossenschaft; Recht; USA; Agriculture, Cooperative -- Law and legislation -- United States; Raisin industry -- California -- Law and legislation; Geschichte 1865-1945.; cooperative farming; cooperatives; landbouw; agriculture; trusts; recht; cooperation; wetgeving; law; geschiedenis; legislation; vs; history; usa; samenwerking; raisins; rozijnen; california; agricultural cooperatives; Agricultural Law (Foreign); Rural History of North America; Agrarisch recht (buitenland); Rurale geschiedenis van Noord-Amerika; Electronic books; History